Air Quality of Indoor Swimming Pools: Are Visits to the Pool as Healthy as Touted? - Chen, Dale; BCIT School of Health Science, Environmental Health (BCIT Environmental Public Health Journal, 2010)
This research project examined the VOC levels in the atmosphere of an indoor pool. The main source of the VOCs within an indoor pool is from chlorination by-products such as chloramines and trihalomethanes. Trihalomethanes has been shown to be carcinogens and chloramines are irritants. There have been numerous reports of increased incidence of breathing problems in frequent swimmers as well as those occupationally exposed. Currently there are no limits established for VOCs within an indoor pool environment. This study involved using a direct reading instrument (VOC meter) to measure the levels of VOCs within a pool. The measurements took place over the course of a day on Dec 21, 2009 from the opening at 6 am to almost closing at 9 pm. The goal was to determine if the levels of VOCs changed over that period of time due to the build up of wastes within the pool, which would have increased voe production. The null and alternate hypotheses are as follows H0 : There is no difference in the VOC levels during the different times of day within an indoor swimming pool's atmosphere when measured by a handheld VOC meter. Ha: There is a difference in the VOC levels during the different times of day within an indoor swimming pool's atmosphere when measured by a handheld VOC meter. This hypothesis was tested via an ANOVA. Also, since numerous readings were taken anyway, readings were taken at different distances from the water surface in order to perform a regression analysis to see if there is a correlation between the distance from the water surface and VOC levels. It was determined that there was a significant difference in VOC levels during the different times of day within an indoor swimming pool's atmosphere when measured by a handheld VOC meter. However, there was no relationship found between the distance from the pool surface and the VOC levels.